A comparative study of lapping and grinding induced surface/subsurface damage of silicon wafers and corresponding polishing efficiency. (18th September 2020) - Li, Zhiyuan; Gao, Shang; Kang, Renke; Li, Honggang; Guo, Xiaoguang
The lapping and grinding induced wafers surface damage layers with the same roughness Ra were compared in terms of surface morphology, surface roughness PV, subsurface damage, material removal mechanism, and material removal rate of later chemical mechanical polishing. The results indicated that surface material on silicon wafer lapped using loose abrasive was removed in brittle mode, and that ground using diamond wheel was removed in both brittle mode and ductile mode. The silicon wafer produced by lapping and grinding had almost the same surface roughness Ra, however, the corresponding surface roughness PV induced by lapping was less than that induced by grinding. When using the chemical mechanical polishing to remove damage layer generated by lapping and grinding, the surface roughness Ra of lapped wafer decreased faster than that of ground wafer, but the material removal rate of lapped wafer was higher than that of ground wafer. Discussion was provided to explore the influence of surface morphology on material removal rate during polishing.